(untitled) (Journal of the College of Basic Education, 2022)
The aim of the Current research is to know The availability of higher educational goals in discussing the subjects of the Glorious Qur’an and Islamic Education for the sixth preparatory, according to Bloom’s, The researcher adopted the method of content analysis by considering the question as a unit of analysis, The objectives were extracted from the paragraphs of the questions discussing the topics, and it was found that they relied on the lower educational goals of the knowledge domain only, as the level of understanding reached the highest level, at a rate of (50%), As for the lowest level in the higher educational goals is almanac and reached (2.8%), This is unacceptable for a finished preparatory and its students are on the way to the university, The research reached a conclusion that the book of the Glorious Quran and Islamic Education is the sixth grade preparatory, He neglected the higher levels of educational goals in addition to the other two areas - skill and emotional - and did not address them even with a simple thing.